Geomechanical modeling and wellbore stability analysis for studying the shale rock failure - Noori, Ahmed Faris; Hadi, Farqad (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Wellbore stability constitutes a critical challenge that can precipitate an escalation in non-productive time (NPT) during drilling operations, subsequently resulting in an increase in well expenditures and consequent revenue deficits. Shale formations exhibit a greater propensity than many geological formations to induce complications during the drilling process. Consequently, advanced geomechanical analyses were executed on select wells within the Zubair oilfield to clarify the fundamental causes of instability predominant in the field. In this study, the model was applied to two specific wells (ZB-A and ZB-B) to perform a wellbore stability assessment utilizing available well log data, which includes parameters such as bit size (BS), caliber (CAL), shear sonic logs (DTS), compressional sonic logs (DTC), and gamma ray (GR) logs. Laboratory-derived data in addition to the minimum horizontal stress that were refined using the leak-off test (LOT) measurements. The predicted formation pore pressures were calibrated against the pore pressure readings obtained from a repeated formation tester (RFT). The Mogi-Coulomb failure criteria were employed to ascertain the safe operating mud window requisite for balanced drilling, owing to the criterion’s capacity to accommodate the intermediate principal stress (σ2). The proposed mud weight values, derived from the model, range from 1.32 g/cc to 1.45 g/cc, whereas a mud weight of 1.19 g/cc was utilized during the drilling operations. The findings of this research can be used as a guide to choose the best mud weight to solve problems related to wellbore instabilities in this field.